Potential Applications of Nanoparticles for Hyperthermia - Quini, Caio Cesar [UNESP]; Krishnan, Sunil; Asea, AAA; Almasoud, N. N.; Krishnan, S.; Kaur, P. (Springer, 2015)
There is converging evidence that clinical mild temperature hyperthermia sensitizes tumors to conventional therapies as chemotherapy and radiation therapy. Coupled with an increasing understanding of the biological basis of this synergy there has been a parallel increase in the ability to achieve, maintain, measure and monitor temperature and its physiological and physical consequences. A new entrant in the arena of hyperthermia generation is nanotechnology which capitalizes on locally injected or systemically administered nanoparticles that home to tumors and are activated by extrinsic energy sources to generate heat. This chapter highlights the unique opportunities and challenges with implementing hyperthermia mediated by a variety of engineered nanoparticles for cancer therapy.
Keywords: Nanoparticles; Hyperthermia; Radiation; Cancer; Immunity